(3efJgi GdEQGOGJ aj LeY GdebfY eY GdJfbjMs - (3eMeO Hf CMeO Hf YHO GdYRjR GdaJhMi GdMfHdis; (3YHO Gddg Hf CMeO Hf bOGeI GdLeGYjdj GdebOSj GdOeTbj GdMfHdj GdebOSj, GHf bOGeI , ehab GdOjf, CHh eMeO,J (B620 (3g` s
(3ChdgG (B:s
(3hHYO aGdJfbjM GdeJHY ai JMQjQ CMcGe GdebfY ai Gdabg s
(3BNQgG (B:s
(3bO LeY aGhYi hSYi ai JMUjd GdaVGjd adG NjH Gddg dg gPG GdeSYi s
(3HgG fXGe GdJYbjHIs
(3Ydjg hbas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCRgQ s
Keywords: (3Gdabg GdMfHdjs